HUBUNGAN TINGKAT PENGETAHUAN TENTANG MENOPAUSE DENGAN DUKUNGAN SOSIAL SUAMI SAAT ISTRI MENGHADAPI MENOPAUSE DI DESA SOMAGEDE KECAMATAN SOMAGEDE BANYUMAS - Wulandari, Indah Yuliana; Djannah, Sitti Nur; Utami, Isti Ken (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2009)
Background: The knowledge of husband fowards menopause will help women to understand and prepare themselves in the period of menopause. Normally women will experience menopause between the ages of 45 years and 50 years. Support from her husband when the wife entering menopause can increase the confidence and the spirit of living of the wife, so that they will get a harmonic family in facing their elderly life. Goal of this research is to understand the relationship between the level of knowledge on menopause and social support of husband while the wife entering menopause in the Village of Somagede, Somagede sub district, Banyumas Regency Method: This was an observational analytic research using  cross sectional approach . The simple of this research were 70 respondents. Data collections for primary data used questionnaire.  Results: There is a relationship between the level of knowledge on menopause and social support of husband when his wife entering menopause with correlation coefficient value (R) = 0, 523 and R square 0, 273, and a significant value (Sig) = 0,000 lower than the alpha value (?), then Ha that there was a connection between the levels of knowledge about menopause with social support while the wife of the husband menopause is "received". Conclusion: There was a relationship between the level of knowledge about menopause and social support of husband when the wife entering menopause. The level of knowledge about menopause contributes 27,3 percent of the social of support the husband when the wife entering menopause in Somagede village, Somagede sub district, Banyumas Regency. Keywords: Knowledge, Menopause, Age